2001
DOI: 10.1002/1521-3757(20010903)113:17<3241::aid-ange3241>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Ungewöhnliche Bildung eines Azaphospholens aus 1,3,4,5-Tetramethylimidazol-2-yliden und Diisopropylaminophosphaethin

Abstract: Bei ersten Studien zur Reaktivität von N-heterocyclischen Carbenen [1] gegenüber Phosphaalkinen fanden wir vor kurzem, dass die anellierte Verbindung N,N'-Bis(2,2-dimethylpropyl)benzimidazolin-2-yliden 1 [2] mit PCtBu 3 a quantitativ zum Triphosphol 4 a und mit PCNiPr 2 3 b zum 1,2,3-Triphospheten 5 reagiert. [3] Parallel hierzu erhielten Nixon et al. [4] das Triphospholderivat 4 b durch die Umsetzung des Arduengo-Carbens 1,3,4,5-Tetramethylimidazol-2-yliden 2 mit 2,4,6-Tri-tert-butyl-1,3,5-triphosphabenzol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Furthermore, the molecular structure of the NHC‐stabilized borane complex 4 confirms the cleavage of one B−H bond and formation of the Ga−H bond, which is most likely caused by the activation of an acidic B−H bond of a BH 3 molecule due to the formation of a covalent B−P bond in 4 . The P−B bond lengths of 4 range from 1.9471(16) Å to 1.9763(15) Å and agree with the sum of the calculated single‐bond radii (P 1.11 Å; B 0.85 Å), [27] and experimentally observed P−B single‐bonds in IPr(PPh)(BH 3 ) 2 (1.945(2)/1.948(2) Å), [38] [(IPr)P] 2 BH 2 (1.972(4)/1.982(4) Å) [39] and other known P−B single bonds (1.934(5)/1.953(6) Å) [40] …”
Section: Resultssupporting
confidence: 79%
“…Furthermore, the molecular structure of the NHC‐stabilized borane complex 4 confirms the cleavage of one B−H bond and formation of the Ga−H bond, which is most likely caused by the activation of an acidic B−H bond of a BH 3 molecule due to the formation of a covalent B−P bond in 4 . The P−B bond lengths of 4 range from 1.9471(16) Å to 1.9763(15) Å and agree with the sum of the calculated single‐bond radii (P 1.11 Å; B 0.85 Å), [27] and experimentally observed P−B single‐bonds in IPr(PPh)(BH 3 ) 2 (1.945(2)/1.948(2) Å), [38] [(IPr)P] 2 BH 2 (1.972(4)/1.982(4) Å) [39] and other known P−B single bonds (1.934(5)/1.953(6) Å) [40] …”
Section: Resultssupporting
confidence: 79%
“…The bicyclic azaphospholene product of this reaction is formed by unusual CÀ H activation at the nitrogen substituent of the NHC. [17] Similar to polyphosphines, other polyphosphorus compounds such as Na 3 P 7 or (Me 3 Si) 3 P 7 also provide access to NHC-phosphinidenes of NHCs of varying steric demand by reaction with dihydroimidazolium chlorides, as reported by Grützmacher and Gudat et al [15] Moreover Hey-Hawkins and co-workers demonstrated that Na 2 (THF) 4 P 4 Mes 4 is a suitable precursor for (Me 2 Im)PMes, if reacted with Me 2 Im or [Me 2 ImÀ H] + I À . [18] We recently explored the reactivity of NHCs and related molecules with group 13 to 15 main group element hydrides [19] and other main group element compounds.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, several transition metal complexes of the NHC-phosphinidene 1 were synthesized. In situ prepared [W(CO) 5 (thf)] reacts with 1 quantitatively to yield [{(iPr 2 Im)PPh}W(CO) 5 ] (15), the reaction of 1 with [Co(CO) 3 NO] results with CO release in the formation of [Co{(iPr 2 Im)PPh}(CO) 2 (NO)] ( 16) and the reaction of [(C 5 Me 5 ) Co(η 2 -C 2 H 4 ) 2 ] with 1 afforded [(η 5 -C 5 Me 5 )Co{iPr 2 Im)PPh}(η 2 -C 2 H 4 )] (17). Both cobalt complexes, [Co{(iPr 2 Im)PPh}(CO) 2 (NO)] ( 16) and [(η 5 -C 5 Me 5 )Co{iPr 2 Im)PPh}(η 2 -C 2 H 4 )] ( 17) are stable in the solid state and in solution at room temperature, but decompose to the NHC complexes [Co(iPr 2 Im)(CO) 2 (NO)] and [(η 5 -C 5 Me 5 ) Co(iPr 2 Im)(η 2 -C 2 H 4 )], respectively, and cyclo-oligophosphines upon heating to 80°C in solution.…”
Section: Discussionmentioning
confidence: 99%
“…5 DFT calculations show that 9 is the result of the stabilization of the intermediate 8 through intramolecular C H insertion into the methyl group of the amino substituent of carbene 2. The bonding situation in the new azaphosphole 9 is best described by the two resonance structures 9A and 9B, in which 9B represents an inversely polarized phosphaalkene with a π -electron distribution P δ− -C δ+ at the P C double bond.…”
mentioning
confidence: 99%